Perancangan Arsitektur Sistem Informasi Menggunakan Metode Agile Dengan Kerangka Kerja Scrum Pada Pelayanan Instalasi Gizi RSUD. Ciamis - Maulana Sidiq; Rian Dwicahya Supriatman; Eryan Ahmad Firdaus; Bacilius Agung Suburdjati (NUANSA INFORMATIKA, 2024)
A hospital nutrition service is an inseparable part of other health services in hospitals, besides that nutrition service is an effort to improve the quality of health services for inpatients or outpatients in hospitals. In implementing the Scrum work frame in the architectural design of the nutrition service information system at the Regional Public Hospital Ciamis (RSUD. Ciamis) it is expected to produce products that are in accordance with the client's needs. The stages from preparation (Initialization), making a product backlog, making a sprint backlog to the execution stage of this method indicate an iterative method because it prioritizes product functions. The Scrum framework implements work functions according to its role, namely the Product Owner who is fully responsible for the products that it produces, the Development team is responsible for project work, and the Scrum master is the person who controls so that the implementation of the work does not go out of the rules of the Scrum game. The results of designing an information system with application development, this research uses the scrum framework which is carried out with 3 sprints with the estimated processing time for each sprint as follows: sprint 1 reaches 30 days, sprint 2 reaches 27 days and sprint 3 reaches 30 days. According to the rules of the scrum framework, each sprint should not exceed one month so that the project can be implemented quickly and produce the desired results